Let $ (R,+,\cdot) $ be a ring that has at least two invertible elements. Let $a,b$ be two invertible elements such that $$ord(a)=ord(b)=+\infty$$ Let consider the following sequence $$c_n=a^n-b^n$$ Let $S=\{c_1,c_2,...,c_m,...\}$ a set of elements from $R$.

Prove that if $S=\{c_1,c_2,...\}$ is finite then $$0 \in S$$


I obtained that:

$$a^n-b^n=c_n$$ then $$a^{n+1}-ab^n=ac_n$$ and $$a^{n+1}-b^{n+1}=c_{n+1}$$ then $$(b-a)b^{n}=ac_n-c_{n+1}$$ Since $S$ is finite then $$M=\{ac_n-c_{n+1},n \in \mathbb Z_+\}$$ is finite.

So $$\{(b-a)b^n,n \in \mathbb Z_+\}$$ is finite. Then there exists $i$ and $j$ such that $$(b-a)b^i=(b-a)b^j$$

How should I continue with this. I would highly appreciate somebody's help.

  • 1
    $\begingroup$ Is there a connection to this question you had before? $\endgroup$ May 14 at 18:14
  • 2
    $\begingroup$ Is the ring assumed to be commutative? $\endgroup$ May 14 at 21:46
  • $\begingroup$ No, the ring is not commutative. $\endgroup$
    – shangq_tou
    May 15 at 6:50

1 Answer 1


Modified to NOT assume $R$ is commutative

Continuing from where you left off, you could use your line of reasoning to show the following: For any positive integer $l$ [not just $l=1$], there is a positive integer $k_l$ such that $$(a^{k_l}-1)c_l = 0.$$ [Indeed for each such $l$ there exists distinct integers $i$ and $j$ such that $a^ic_l = a^jc_l$, and assume $j >i$. Then $k_l=j-i$ works.] Furthermore, $(a^k-1)c_l =0$ for any $k$ that is a multiple of $k_l$, because even in a noncommutative ring, $(a^{C_1}-1)$ and $(a^{C_2}-1)$ commute for any two integers $C_1$,$C_2$. So let $T$ be a finite set of integers $l$ such that for all $m \in \mathbb{N}$ there is an $l \in T$ such that $c_m=c_l$, and set $$k = \prod_{l \in T} k_l.$$ Then $$(a^k-1)c_m = 0 \ \forall m \in \mathbb{N}.$$

In fact, for any multiple $K$ of $k$, it follows that $$(a^K-1)c_m =0 \ \forall m \in \mathbb{N}.$$ Thus we conclude with the following:

Claim 1 There is a positive integer $k \in \mathbb{N}$ such that the equation $$(a^K-1)c_m=0 \ \forall m \in \mathbb{N}$$ holds for all multiples $K$ of $k$.

We also make the following claim:

Claim 2 There exists a multiple $K$ of $k$ and a positive integer $n$ such that the equation $c_{n+K}=c_n$ holds.

Proof: Let $N$ be the number of distinct $c_l$; $l \in \mathbb{N}$. Then for any positive integer $m$, at least two of $c_m, c_{m+jk}$; $j=1,2,\ldots, N$; must be the same by the Pigeonhole Principle. ■

So, using Claims 1 and 2, let $K$ be a multiple of $k$, where $k$ is as in Claim 1, and let $n$ be an integer such that the equation $c_n=c_{n+K}$ holds.

Then simple algebra gives $$a^Kc_n +a^Kb^n -b^{n+K} = c_{n+K}.$$ plugging into this the equation $c_n=c_{n+K}$ and rearranging gives $$(a^K-1)c_{n+K} + c_Kb^n = 0.$$ But, as $K$ is a multiple of $k$ as in Claim 1, the equation $(a^K-1)c_{n+K}=0$ holds, so we are left with the equation $$c_Kb^n = 0.$$ As $b^n$ is invertible, it follows that the equation $$c_K=0$$ must hold. ■

  • $\begingroup$ For the equation $$ a^Kc_n +a^Kb^n -b^{n+K} = c_{n+K} $$ can you provide a little more detail? $\endgroup$
    – quasi
    May 16 at 8:51
  • $\begingroup$ $$a^Kc_n +a^Kb^n-b^{n+K}$$ $$= a^K(a^n-b^n)+a^Kb^n-b^{n+k}$$ $$= (a^{K+n}-a^Kb^n)+a^kb^n-b^{n+K}$$ $$=a^{K+n} -a^Kb^n+a^kb^n -b^{n+K}$$ $$=a^{n+K}-b^{n+K}$$ $$= c_{n+K}$$. $\endgroup$
    – Mike
    May 16 at 15:27
  • $\begingroup$ @quasi here it is in the above comment $\endgroup$
    – Mike
    May 16 at 15:41
  • 1
    $\begingroup$ Got it. Thanks.${}{}{}{}{}{}{}$ $\endgroup$
    – quasi
    May 17 at 2:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.